The Image of BREAD in Lithuanian Dictionaries - Smetonienė, Irena (Vilnius University Open Series, 2021)
The bread in one form or another has been known to people all over the world. Linguistic data and rites show that the Lithuanians have been eating bread since ancient times. Bread is mentioned in the small-form verbal folklore, songs, sagas, fairy tales, beliefs and various rites. In ancient times the bread was personalised and deified. The examples from the dialect dictionaries were also included into the research because every dialectal saying is an example of cultural message, manifestation of tradition nurturance and preservation, a part of cultural heritage, which links the past with the present. The dialectal examples show, what is deep-rooted in the tradition, what is passed down from generation to generation, what lies in the traditional value system and what makes the essence of an ethnic group. Due to these reasons the dialectal texts have a huge public or cultural value as they denote a content that is significant to a certain community. Having completed the analysis of dialectal discourse, it can be stated that various dictionaries construct the following picture of the concept bread: bread is the main meal of people, it is baked from different kinds of cereal flours, it is respected and saved, it has healing powers; the bread baked at home is the most delicious; if there is no bread, a person starves; to have bread all the time one has to work hard because baking bread is labour-intensive work, which has to be performed with knowledge and love, to make bread delicious and fragrant, calamus, cabbage or maple leaves are put under a loaf of bread, it is decorated or marked with sacred signs; an individual equals bread with human activity and appearance; bread is a measure of life, a reference point for evaluating certain actions. The place of bread in the human life is reflected by derivates as well: special things, capacities for mixing, souring, baking, slicing or keeping bread; other meals prepared from bread.